Project owners – overlooked factors of uncertainty in the example of a water infrastructure improvement project? - Kazbekov, Jusipbek S.; Wegerich, Kai; Yakubov, Murat; Musayev, Sardorbek; Akramova, Indira (Elsevier, 2015)
Donor sponsored projects are often criticized for the tendency to impose standardized institutional and technical solutions in irrigation. Although, this might be the case, a project is based on internal actors, ‘project owners’, who influence solutions and implementation processes. Little attention has been paid to project owners, internal dynamics and how these shape aid projects. In this paper, a water user associations (WUAs) project in Central Asia is explored, which introduced flow regulating and metering devices (hydroposts). It is explored how change within project owners, differences in their interests and absence of a proper knowledge management system within the project influenced the alteration of project objectives, causing failure of the implementation process. The paper concludes that internal dynamics within projects are the main source of project uncertainty and risk. Some recommendations are offered how these risks can be minimized.